Association of Plasma Total Tau Level With Cognitive Decline and Risk of Mild Cognitive Impairment or Dementia in the Mayo Clinic Study on Aging - Mielke, Michelle M. (JAMA Neurol, 2017)
IMPORTANCE: The utility of plasma total tau level as a prognostic marker for cognitive decline and dementia is not well understood. OBJECTIVES: To determine (1) the association between plasma total tau level, cognitive decline, and risk of mild cognitive impairment (MCI) and dementia; (2) whether this association differs by the presence of elevated brain amyloid β (Aβ); and (3) whether plasma total tau level is associated with cognitive decline over a short interval of 15 months. DESIGN, SETTING, AND PARTICIPANTS: The present analyses included 458 participants who were enrolled in a population-based cohort study between October 2008 and June 2013. All included participants had available plasma total tau levels, Aβ positron emission tomography imaging, and a complete neuropsychological examine at the same visit, as well as at least 1 follow-up visit. EXPOSURES: Concentration of plasma total tau. MAIN OUTCOMES AND MEASURES: Risk of MCI and dementia; global and domain-specific cognitive decline. RESULTS: Of the 458 participants, 287 (62.7%) were men; mean (SD) age was 80.6 (5.6) years. Among cognitively normal (CN) participants oversampled for elevated brain Aβ, both the middle (hazard ratio [HR], 2.43; 95% CI, 1.25-4.72) and highest (HR, 2.02; 95% CI, 1.01-4.06) tertiles of plasma total tau level, compared with the lowest, were associated with an increased risk of MCI. Among participants with MCI, higher plasma total tau levels were not significantly associated with risk of dementia (all-cause dementia or Alzheimer disease). Among all participants, higher levels of plasma total tau, examined as a continuous variable, were associated with significant (P < .05) declines in global cognition, memory, attention, and visuospatial ability over a median follow-up of 3.0 years (range, 1.1-4.9 years). In additional analyses restricting the follow-up to 15 months, plasma total tau did not predict decline among CN participants. However, among participants with MCI, higher plasma total tau levels were associated with greater decline in both visuospatial ability (regression coefficient [b] = −0.50 [0.15], P < .001) and global cognition (b = −0.27 [0.10], P = .009) at 15 months. Adjusting for elevated brain Aβ did not attenuate any association. There was no interaction between plasma total tau level and brain Aβ for prognosis with any outcome. CONCLUSIONS AND RELEVANCE: These results suggest that elevated plasma total tau levels are associated with cognitive decline, but the results differ based on cognitive status and the duration of follow-up. The association between plasma total tau levels and cognition is independent of elevated brain Aβ.